ENFLUENCE OF WORKPLACE CONFLICTS, ROLE OVERLOAD TO PHYSICAL DECLINE, PSYCHOLOGICAL AND NURSE PERFORMANCE IN MUHAMMADIYAH HOSPITALS AT KEBUMEN DISTRICT CENTRAL JAVA - Basirun, B; Yuniar, Isma; Agustin, Ike Mardiati (Jurnal Ilmiah Kesehatan Keperawatan, 2018)
Work conflict can lead to physical and psychological decline of employees. The demands of these various roles produce tension that is overload. role overload has a negative effect on performance. On the other hand work conflict does not affect performance. This becomes interesting whether work conflict, overload and decreased physical and psychological affect performance. The purpose of this study was to determine the effect of work conflict on the decreasing physical and psychological abilities of nurses, the influence of the excess role of nurses in decreasing the physical and psychological impairment of nurses, the effect of decreasing nurses' physical and psychological abilities on performance, the influence of nurse-work family conflict on performance, and the influence of the excess role of nurses on performance.The method in this study is a survey by distributing questionnaires to nurses in the inpatient room in 4 Muhammadiyah hospitals in Kebumen Regency, out of 350 respondents only 216 questionnaires were collected. Analysis of the data used is using SEM Amos 22.00. The results showed that there was an influence of overload variable on performance while work conflict did not affect performance. Variables of physical and psychological impairment abilities do not affect performance and do not mediate overload variables or work conflict variables.